2015
DOI: 10.1136/bmjqs-2015-004265
|View full text |Cite
|
Sign up to set email alerts
|

One size fits all? Mixed methods evaluation of the impact of 100% single-room accommodation on staff and patient experience, safety and costs

Abstract: Background and objectivesThere is little strong evidence relating to the impact of single-room accommodation on healthcare quality and safety. We explore the impact of all single rooms on staff and patient experience; safety outcomes; and costs.MethodsMixed methods pre/post ‘move’ comparison within four nested case study wards in a single acute hospital with 100% single rooms; quasi-experimental before-and-after study with two control hospitals; analysis of capital and operational costs associated with single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
245
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(254 citation statements)
references
References 33 publications
9
245
0
Order By: Relevance
“…Numerous efforts have been made to study patient and staff outcomes in relation to specific design characteristics or interventions, including room occupancy (e.g., Maben et al, 2016), the acoustic environment (e.g., Shield, Shiers, & Glanville, 2016), visual contact with nature/landscapes (e.g., Ulrich, 1979), sound and lighting (e.g., Voigt et al, 2017), ergonomic design (e.g., Knibbe & Waaijer, 2012), and the work environment (e.g., Lee & Scott, 2018). Robust research indicates that the design of the care environment has implications for patient safety, communication, coping and experience of stress (Andrade, Lima, Devlin, & Hernandez, 2016; Ulrich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been made to study patient and staff outcomes in relation to specific design characteristics or interventions, including room occupancy (e.g., Maben et al, 2016), the acoustic environment (e.g., Shield, Shiers, & Glanville, 2016), visual contact with nature/landscapes (e.g., Ulrich, 1979), sound and lighting (e.g., Voigt et al, 2017), ergonomic design (e.g., Knibbe & Waaijer, 2012), and the work environment (e.g., Lee & Scott, 2018). Robust research indicates that the design of the care environment has implications for patient safety, communication, coping and experience of stress (Andrade, Lima, Devlin, & Hernandez, 2016; Ulrich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In single bedrooms the staffs is often the patient's main contact given that most patients stay in their room. According to Maben et al patients rarely use dayrooms and therefore interactions with other patients are often absent in wards with only single bedrooms [10]. In conclusion, knowledge about patient's admission in a single bedroom versus a multi bedroom is insufficient and even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, other studies have shown that there seems to be a connection between hospital interior design such as light, music, art on the walls etc and patients' perception of pain, anxiety and length of hospital stay [4][5][6]. Reviews about evidence based health care design conclude that single bedrooms decrease infection rate and promote healing and sleep quality [7][8][9] although conflicting results on infection rate reduction are found by others [3,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps another apparently common sense intervention is the introduction of single-room accommodation, the impact of which in a hospital based in the English NHS is evaluated by Maben et al 3. By moving staff and patients to a nearby, newly built hospital, the cost and disruption likely to result from converting a hospital from traditional wards and bays to single rooms were avoided, making this intervention relatively straightforward.…”
mentioning
confidence: 99%